Prophylactic antibiotics may not be necessary for transoral endoscopic thyroidectomy - Lee, Jun Sung; Kim, Hee Jun; Lee, Jin Seok; Yun, Hyeok Jun; Lee, Suji; Cheong, Jae-Ho; Kim, Soo Young; Kim, Seok-Mo; Chang, Hojin; Lee, Yong Sang; Park, Cheong Soo; Chang, Hang-Seok (Frontiers in Surgery, 2022)
Background With the recent advances in thyroid cancer surgery techniques and the increasing number of patients concerned about cosmetics, the use of transoral endoscopic thyroidectomy is increasing globally. The aim of this study was to determine whether transoral endoscopic thyroidectomy is truly a clean-contaminated surgery. Methods From September 2016 to April 2018, 20 patients with thyroid cancer underwent transoral endoscopic thyroidectomy performed by a single surgeon at Gangnam Severance Hospital. Before and after surgery, the oral cavity was swabbed to obtain culture samples, and antibiotics were administered before and after surgery each once. Results Of the total 20 patients, no bacteria were identified before or after surgery in eight (40%) patients. Bacteria were identified both before and after surgery in seven patients (35%). In four patients (20%), bacteria were not identified before surgery, but bacteria were identified after surgery. Bacteria were identified before surgery but not after surgery in one patient (5%). No surgical site infection was observed. All the bacteria identified were normal flora of the oral cavity and skin. Conclusions There was no difference between the preoperative culture and postoperative culture of the oral cavity in patients undergoing TOET, and there were no postoperative surgical site infection with prophylactic pre & post-operative antibiotics use. Considering the patient's position and surgical extent in TOET, it appears to be difficult for non-indigenous bacteria to invade the surgical site in oral cavity.